Endoscopic full thickness resection versus submucosal tunneling endoscopic resection for removal of submucosal tumors: a review article - Dellatore, Peter; Bhagat, Vicky; Kahaleh, Michel (Translational Gastroenterology and Hepatology, 2019)
Submucosal tumors (SMT) are protuberant lesions with intact mucosa that have a wide differential. These lesions may be removed by standard polypectomy, endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), or surgically. However, in lesions that arise from the muscularis propria, full thickness resection is recommended. This can be completed using either endoscopic full thickness resection (EFTR) or submucosal tunneling endoscopic resection (STER). EFTR can be accomplished by completing a full thickness resection followed by defect closure or by securing gastrointestinal wall patency before resection. STER is an option that first creates a mucosal dissection proximal to the lesion to allow a submucosal tunnel to be created. Using this tunnel, the lesion may be resected. When comparing STER to EFTR, there was no significant difference when evaluating tumor size, operation time, rate of complications, or en bloc resection rate. However, suture time, amount of clips used, and overall hospital stay were decreased in STER. With these differences, EFTR may be more efficacious in certain parts of the gastrointestinal tract where a submucosal tunnel is harder to accomplish.